2022
DOI: 10.1101/2022.04.04.22273172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early SARS-CoV-2 reinfections within 60 days highlight the need to consider antigenic variations together with duration of immunity in defining retesting policies

Abstract: The emergence of the SARS-CoV-2 Omicron variant, characterized by a significant antigenic diversity compared to the previous Delta variant, had led to a decrease in antibody efficacy in both convalescent and vaccinees sera resulting in high number of reinfections and breakthrough cases worldwide. However, to date, reinfections are defined by the ECDC as two positive tests >/= 60 days apart, influencing retesting policies after an initial positive test in several European countries. In our manuscript, we ill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…First, it is important to acknowledge the study selection procedures when interpreting the risk estimates. Restricting the analysis to hospitalized patients may hamper both external and internal validity [57,59,60]. Further, the hospitalized patients with available information on the SARS-CoV-2 variant of their infection may not be representative of the hospitalized population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is important to acknowledge the study selection procedures when interpreting the risk estimates. Restricting the analysis to hospitalized patients may hamper both external and internal validity [57,59,60]. Further, the hospitalized patients with available information on the SARS-CoV-2 variant of their infection may not be representative of the hospitalized population.…”
Section: Discussionmentioning
confidence: 99%
“…Having exhaustive information on the vaccination status, and performing a sensitivity analysis excluding patients with a documented previous infection, enabled us to account, to a large extent, for the gradually changing background immunity in the population. However, the number of documented reinfections, defined as two positive tests in the same individual taken more than 90 days apart, is probably an underestimation given the larger antigenic diversity of Omicron [59]. The effects of undocumented previous infections and the fact that the rate of underascertainment varies considerably over time could potentially hamper the comparison.…”
Section: Discussionmentioning
confidence: 99%
“…3 Omicron BA.2 reinfections had been documented using whole genome sequencing as early as 20 days following an Omicron BA.1 primary infection, although such occurrences appeared rare. 16,17 We observed a moderate protection against any (38%) and symptomatic infection (51%) by heterologous pre-Omicron primary infection without vaccination, but a higher estimate for two-dose hybrid immunity (81%). An study from Qatar reported a 46% effectiveness against symptomatic BA.2 infection in individuals with pre-Omicron PI and 55% and 77% if combined with two-or threedose vaccination, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…We defined reinfections based on a ≥30-day interval between positive tests because of data documenting early reinfections during SARS-CoV-2 variant replacement periods. 16,17 Prolonged viral shedding might have been misclassified as reinfections, 27 but this would tend to underestimate the protection associated with prior BA.1 infection. Reassuringly, sensitivity analysis using the standard ≥90-day interval did not change our estimates of protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation